do it by shreedharacharya
Attachments:
![](https://hi-static.z-dn.net/files/db8/86ebf899a41bb862f9d61b52b764ba11.jpg)
Answers
Answered by
0
Answer:
Step-by-step explanation:
★ Brainly Teacher ★
(m/n)x^2 +(n/m) = 1-2x
(m/n)x^2 +2x =1-(n/m)
x^2 +2(n/m)x =n/m -n^2/m^2
add (n/m)^2 both side
x^2 +2.(n/m).x +(n/m)^2 =n/m -n^2/m^2+n^2/m^2
(x+n/m)^2 =n/m
take square root ,
x + n/m = +_ √(n/m)
x = -n/m +_√(n/m)
Read more on Brainly.in - https://brainly.in/question/1110968#readmore
Answered by
33
Answer:
Solve the following quadratic equations by factorization: (m/n)x^2+n/m=1-2x - Sarthaks eConnect | Largest Online Education Community
Now, one of the products must be equal to zero for the whole product to be zero. Hence we equate both the product to zero. In order to find the value of x. Therefore,
Step-by-step explanation:
hopes it helps you
Attachments:
![](https://hi-static.z-dn.net/files/d9b/8459dcd51d24ebf63d7f12e547f387f6.jpg)
![](https://hi-static.z-dn.net/files/dc4/003ce876c85014fab14b6cf23d0ab71a.jpg)
![](https://hi-static.z-dn.net/files/d33/1363b20f647043e0a4f2570b46e80be5.jpg)
Similar questions